A new approach for decreasing energy in wireless sensor networks with hybrid LEACH protocol and fuzzy Cmeans algorithm. (2015) - Bouyer, Asgarali; Hatamlou, Abdolreza; Masdari, Mohammad
The optimum use of energy in wireless sensor networks (WSNs) is very important. The recent researches show that organising the network nodes in some clusters leads to higher efficiency of energy and finally it increases the lifetime of the network. So, controlling the number and the location of the clusters head (CHs) and also the size of the clusters about the node number leads to a balance in energy use of the CHs and increasing the lifetime of the network. Clusteringbased routing protocols are energyefficient protocols that improve the lifetime of a wireless sensor network. The objective of the clustering is to minimise the total transmission power by aggregating into a single path for prolonging the network lifetime. In this paper, fuzzy Cmeans (FCM) algorithm is used for the optimum number of the CHs and their location. Using FCM in WSNs helps changing the LEACH protocol parameters while execution. The results show that the hybrid algorithm increases the lifetime of the network in comparison to the LEACH algorithm.